Men’s participation during pregnancy, childbirth and postpartum and - Jannesari, shrareh; Mashhory, azar; Alavi Majd, hamid (Advances in Nursing & Midwifery, 2013)
Background and aim Increasing global approach to men’s participation in care and reproductive health programs, in the past 15 years, has created a need to research on men’s encouragement to take responsibility for their families’ health through Men’s participation. Therefore, the aim the present study is to determine men’s participation in reproductive health care programs during pregnancy, in health clinics affiliated to Shahid Behshti University of Medical Sciences. In 1388. Material & methods: This was a descriptive study on 400 cases that had at least one child under 2 years and familly file in health clinics coverage Shahid Beheshti University. Sampling was multi-stage cluster Nonrandomized and research instrument was a questionnaire Findings According to the findings of the study, the mean age of participant was (37/27±5/56). (60/2 Percent) had a child and pregnancy in (24/8 Percent) was scheduled. Generally (74/2 Percent) men demonstrated good cooperation and participation and (0/25) had relative participation (89/0Percent) men had good knowledge and (11/0 Percent) had relative knowledge. There was Significant relationship between participation and education (p<0/0001), If higher education participation was low. There was Significant relationship between participation and job involvement (p<0/004). There was highest participation (83/9 Percent) in men whose job was lndependent. Also between the term Marriage and Participation was found Significant relationship (p<0/0001). There was Significant relationship between kind of Pregnancy and participation (P<0/0001) if It was planned to increase participation. Conclusions: The results of this research imply good men,s participation during pregnancy and childbirth that showe good oppurtunity for education and counseling before pregnancy that is good oppurtunity for Training men by expert person can enhance men ,s participation during pregnancy and childbirth. Keywords: men’s participation, prenatal care, delivery *Corresponding Author: Sharareh Jannesari, Lecturer, Dept of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Science, Tehran, Iran. E-mail :shararehjannesari@gmail.com Alipoor B Sattari F (2010). [Male participation in prenatal care]. Behvarz Faslname. 19(2)40-41.(Persian) . http://www.magiran.com/temp/mag-pdf/272013/1586-20457240-B91.pdf„ -Carter M, Speizer I (2005). Salvadoran fathers´ attendance at prenatal care, delivery and postpartum care.Revista Panamericana Salud Publica. 18 (3) 149-156 -Dellmann T (2004). The best moment of my life: "A literature review of father’s experience of child birth. Australian Midwifery.17 (3) 20-26. http://www.journals.elsevierhealth.com/periodicals/ausmid/article/PIIS1448827204800142/abstract -Dragonas TG (1992).Greek fathers participation in labour and care of the infant. Scandinavian Journal of Caring Science.6 (3) 151-9. http://www.ncbi.nlm.nih.gov/pubmed/1439376 -Ghandi M (2009). [Male participation in maternal health]. Women´ s mahnameh.147 I 88. (Persian). http://www.magiran.com/magtoc.asp?mgID=1095& -Gruskin S Cottingham J Hilber AM et al (2008).Using human rights to improve maternal and neonatal health: history, connections and a proposed practical approach. Bulletin of the World Health Organization. http://www.who.int/bulletin/volumes/86/8/07-050500/en /print. html (Accessed on 30/05/2010). http://www.who.int/bulletin/volumes/86/8/07-050500/en/index.html Kinanee J Ezekiel-Hart J (2009) Men as partners in maternal health: Implications for reproductive health counselling in Rivers State, Nigeria. African Journal of Psychology and Counseling Vol. 1 (3), pp. 039–044. -Orji EO Adegbenro CO Moses OO etal (2007). Men´ s involvement in safe motherhood. Journal of Turkish- German Gynecology Association.8 (3) 240 -248. -Rahman MM (2009).Factors associated with delivery assistance: Dose differentials exist between Rural and Urban areas in Bangladesh? The Internet Journal of Family Practice 7(2)38-49 -Soul Sista. Inactive (2007). Men: Effective Partners for Safe Motherhood. http://www.nigeriavillagesquare.com/forum/lounge/11259-men-effective-partners-safe-motherhood.html -World Health Organization (2007). Maternal Mortality in 2005: Estimates Developed by UNICEF and UNFPA. Geneva: World Health Organization. http://www.who.int/whosis/mme_2005.pdfw -World Health Organization (2005). The World Health Report: 2005: Make Every Mother and Child Count, World Health Organization, Geneva, 2005 World Health Organization (2002). http://www.who.int/whr/2005/02_ contents_en.pdf -World Health Organization. Programming For Male Involvement in Reproductive Health. Report of the meeting of WHO Regional Advisers in Reproductive Health WHO /PAHO Washington DC, USA, 5–7 September 2001, World Health Organization, Geneva, http://whqlibdoc.who.int/hq/2002